Prototype of Automated Vehicle Window Using the Detection of Raindrop Sensor - Lianage, Asanka; Yasak, Mohd Fuad (Journal of Automotive Powertrain and Transportation Technology, 2023)
This project presents prototype of vehicle window using the detection of raindrop sensor in order to reduce heat trapped in the prototype. This project will investigate the effectiveness of heat dissipation at different opening gap of power window. The climate seasons are almost the same throughout all year. Temperature are uniformly high throughout the year, it can range up to 33? and drop as low as 23?. Meanwhile, the mean annual rainfall of Malaysia is approximately 2540mm. Since high number of houses in Malaysia does not have garage to park their vehicle inside, the temperature of the car cabin can reach a high temperature when the weather is hot. The rise in temperature in the vehicle cabin is caused by the ultraviolet ray from the sun that passes through the window and windscreen of the vehicle. The amount of ultraviolet ray passing through can be reduced by tinting the window but it is not effective. The propose mechanism for the prototype of vehicle window to reduce the interior cabin temperature. Finally, evaluate the effectiveness of the prototype vehicle window mechanism in reducing the interior cabin temperature. Studies will be conducted to investigate the factors of increasing temperature inside the car cabin. A prototype of vehicle window will be built to propose the mechanism. To evaluate the effectiveness of the prototype vehicle window mechanism in reducing the interior temperature is done by conducting 2 experiments. By doing this project, the prototype has proven that the implementation of automated power window to dissipate heat is effective with the use of raindrop sensor.